Response Analysis of Projectile System Under Gaussian Noise Excitation Using Path Integral Method - Wang, Liang; Li, Xinyi; Peng, Jiahui; Zhang, Zhonghua; Dong, Shuangqi (International Journal of Aerospace Engineering, 2024)
During flight, projectiles are subject to uncertainties such as aerodynamic forces, wind gusts, and measurement errors; all of which significantly affect their stability and accuracy. As a result, studying the response of projectile systems under stochastic excitation is essential. This paper focuses on the solution and analysis of projectile system responses under stochastic excitation. We employed the path integral method to compute the transient and stationary probability density functions for projectile systems subjected to Gaussian stochastic external and parametric excitations. Based on the probabilistic responses, we analyzed the evolution of the system’s probability density function over time under Gaussian white noise excitation, as well as the changes in the stationary probability density function with air density and flight speed as bifurcation parameters. The analysis results indicate that within a specific range of parameter variations, air density can induce stochastic P‐bifurcation phenomena. Furthermore, increasing air density and flight speed can enhance the stability of the projectile.